USE OF CAD SYSTEMS IN THE DESIGN OF GRAIN INDUSTRY ENTERPRISES - SOKOLOVSKA, OLENA; VALEVSKA, LIUDMYLA; TSIUNDYK, OLEKSANDR; BORDUN, TATIANA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article considers the main aspects of using CAD systems in the design of grain industry enterprises, which is a key factor in increasing the efficiency, accuracy and speed of development of design documentation. The functional capabilities of modern CAD systems are analyzed, their impact on the optimization of technological processes and integration with other information systems, such as BIM (Building Information Modeling), CAE (Computer-Aided Engineering) and PLM (Product Lifecycle Management). An overview of modern CAD systems used in industrial design is presented, including AutoCAD, SolidWorks, Revit, Bentley OpenPlant, AVEVA PDMS and others. Their advantages in creating complex digital models of enterprises, including 2D drawings, 3D modeling and parametric design, which provides detailed visualization of structures and technological equipment, are noted. Special attention is paid to the integration of CAD systems with other information technologies. The use of BIM technologies for managing the life cycle of construction objects and the possibility of using CAE for engineering calculations of strength, aerodynamics and heat transfer are considered. The role of PLM systems in creating a comprehensive information environment for managing project documentation and coordinating work between different departments is noted. The use of computer-aided design systems in the grain industry has the following advantages: process automation, reducing material costs, minimizing errors at the planning stage and increasing the efficiency of interaction between designers, builders and equipment manufacturers. The conclusions emphasize that the use of modern CAD systems allows significantly improving the quality of design of grain industry enterprises, ensuring flexibility, accuracy and efficiency of all stages of development. Recommendations are offered for the selection of software depending on the specifics of the task and the scale of the project, and the prospects for further development of digital technologies in the design of grain processing complexes are also determined.